Consequences of War: Japan's Demographic Transition and the Marriage Market - Kota Ogasawara; Mizuki Komura (Global Labor Organization (GLO), 2021)
This study explores the effects of imbalances in the sex ratio, and their impact on intra-household bargaining, on both the quantity and the quality of children. We first present the theoretical model of intra-household bargaining in the presence of con icting family goals within a couple, and show that male scarcity (a decrease in the male to female sex ratio) induces an increase in the number of children, but a decrease in the quality of children. Second, using the impact of World War II on the sex ratio, as a quasi-natural experiment, we establish empirically that the decrease in the male to female sex ratio in World War II contributed to a lower decline in fertility and child mortality rates in postwar Japan. In particular, the fertility rate would have fallen by an additional 12% and the child mortality rate by an additional 13% between 1948 and 1970, in the absence of the decrease in the sex ratio.
Keywords: J11; J12; J13; J16; N15; N35; 330; quantity-quality trade-off of children; bargaining power; marriage mar- ket; sex ratio